The application of an effective e-collaborative learning among students in the Authoring Language Subject (SPM 2322) at the Faculty Education, University Technology Malaysia - Ali, Mohd. Fadzli; Atan, Noor Azean; Moh, Hieng Wee (2006)
Nowadays, in the light of new technologies for communication, networking technologies and interactive tools are increasingly being adopted at any educational level. The facilities to communicate using Information and Communication Technology (ICT) are easily available anywhere. Not only is the technology adopted in daily lives but it is also utilised for study purposes. Thus, many tertiary institutions turn to â€œe-learningâ€ as a new mode of study to cope with the increasing number of students when attention to each and every individual becomes a difficult task. This serves a strong reason for the university to adopt an e-learning system so that the communication between students and lecturers will not bind within the confinement of four walls. Instead, it can take place outside the lecture hall and outside office hours through the system. Because e-learning is used to bridge the separation between students and teachers, it has always been associated with distance education. However, e-learning is not only for distance education. E-learning can also be provided in a flexible manner that could also benefit full-time students as well. (Collis & Moonen, 2001). This communication is able to foster on-line communities and could further take many forms of teaching and learning. The researchers are keen to see whether the students would work collaboratively among themselves on the e-learning by applying e-collaborative learning exercises in the subject of SPM 2322 (Authoring Language) at the Faculty Education, University Technology Malaysia. A survey method is used for the research with a sample of 108 students who are currently taking SPM2322 subject. Questionnaires are distributed to the students at the semester end to collect the data needed. The collected data are processed by using Statistical Package for Social Science Version (SPSS), to obtain results in mean and percentage. The research looks at studies two main aspects: to identify (i) how do students collaborate with lecturer, and (ii) how do students collaborate with other students through e-learning system.